CLAY CONDUCTIVITY AND DIFFERENT WATER SATURATION MODELS IN SHALE GAS RESERVOIRS, COOPER BASIN, SOUTH AUSTRALIA - AHMED, WAQAS (2019)
Roseneath and Murteree organic shales, with ultra-low permeability, are the type of unconventional shale gas reservoirs in Cooper Basin, South Australia and are the focus of this research.